Acquired hemophilia due to immune checkpoint inhibitors: A case series introducing emicizumab treatment - Wolff, Louis; Ertl, Carolin; Heinzerling, Lucie; Aspeslagh, Sandrine; Verhaert, Marthe; Lattenist, Raphael; Confente, Caterina; Lambert, Catherine; Ilzkovitz, Maxime (Oncologist, 2025)
Background Acquired hemophilia A (AHA) is a rare but potentially life-threatening autoimmune bleeding disorder and immune-related adverse event (irAE) associated with immune checkpoint inhibitors (ICI). This study discusses 3 new cases of ICI-induced AHA from Belgium and the SERIO-Side Effect Registry Immuno-Oncology (www.serio-registry.org), placing them in the context of existing literature. Methods One case was encountered at a tertiary care center in Belgium. SERIO was queried and yielded another 2 cases. A comprehensive literature review using PubMed identified 8 additional cases. Results A total of 11 patients were analyzed, with a median age of 68 years (range: 56-71), 10 were male. Most (9/11) were treated with anti-PD-1 monotherapy. In 5 cases, toxicity appeared before the fourth cycle. Immunosuppressive therapy successfully achieved complete resolution of AHA in 9 of 11 patients. For the first time, one patient was successfully treated with emicizumab, a monoclonal bispecific antibody, which bridges activated factor IX and factor X. Conclusions Clinicians should be vigilant about ICI-induced AHA as a potentially severe irAE. Prolonged aPTT requires thorough evaluation. Upon AHA confirmation, eradication of anti-FVIII antibodies with corticosteroids, rituximab, or other immunosuppressant should be attempted. Emicizumab offers advantages over traditional replacement therapy, including ease of use and a potential reduction in immunosuppressive drug requirements - an important consideration in ICI-treated patients. Further research is needed to fully understand the pathophysiology and optimize treatment strategy for AHA.
CRIS-Team Scopus Importer:2025-10-16
Keywords: AHA; anti-CTLA4; anti-PD1; anti-PDL1; emicizumab; hemophilia; immune checkpoint inhibitors; immunotherapy